ANALISIS PELAYANAN PERPUSTAKAAN PADA KANTOR PERPUSTAKAAN ARSIP DAN DOKUMENTASI KABUPATEN SIGI - Amal, Ernawati (Katalogis, 2016)
An Analysis of Library Services at the Archives and Documentations Library Office, Sigi Regency. This research aims at determining whether the library services quality of Archives and Documentations Library Office, Sigi Regency can satisfy the library visitors. This is a descriptive qualitative in which this kind of research is used to describe the situation or phenomenon based on real facts at Archives and Documentations Library Office, Sigi Regency. The Informants selection uses two techniques, they are purposive sampling technique, sample selection based on certain considerations, and accidental sampling is a sample selection technique based on whoever met accidentally by the researcher. The data were collected through observations, interviews, and documentations. The research results indicate that the library services in Archives and Documentations Library Office, Sigi Regency viewed from the indicators a) Tangible b) Reliability c) Responsiveness d) Assurance did not run as expected, while Empathy indicator can be categorized as well. It means that the library services quality at Archives and Documentations Library Office is still low and has not been able to satisfy the visitors.